Atomically thin antiperovskite nanosheets for electrocatalysts
The atomic ultra-thin anti-perovskite nanosheet electrocatalyst was prepared by layered precursor stripping derivatization method, which solved the problem of insufficient activity and stability of the nanocatalyst, and achieved high performance and low cost electrocatalytic effect.
Patent Information
- Application Number
- CN202311059990.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-08-22
AI Technical Summary
The mass activity and stability of existing nanocatalysts are insufficient and cannot meet commercial needs. The precious metal catalysts are expensive and have limited stability, making it difficult to achieve high performance and low cost replacement.
The atomic ultrathin anti-perovskite nanosheet electrocatalyst was prepared by layered precursor stripping derivatization method. By mixing glycine and water and adding sodium hydroxide solution, a layered bimetallic hydroxide was formed, and then peeled in the formamide solution and sintered in the presence of sodium chloride to obtain atomic ultrathin anti-perovskite nanosheet with a thickness of 0.4-1.2 nm.
High-performance oxygen reduction and hydrogen precipitation activity are achieved, the stability is better than that of commercial precious metal catalysts, the cost is lower than that of precious metal catalysts, and the synthesis method is simple and universal.
Smart Images

Figure CN117023528B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalysts, and in particular to an atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst. Background Art
[0002] The development of high-performance, low-cost new electrochemical catalysts is the key to many new energy technologies such as water electrolysis for hydrogen production and hydrogen fuel cell PEMFC. The core of water electrolysis for hydrogen production and hydrogen fuel cell technology lies in the electrochemical catalytic performance of their catalysts for oxidation reaction (ORR) and hydrogen evolution reaction (HER). Although the current commercial precious metal platinum / carbon catalysts are highly active, they are expensive and have limited stability, which seriously restricts the popularization and use of the above technologies. It is urgent to seek high-performance and low-cost alternative catalysts.
[0003] At present, oxygen reduction or hydrogen evolution catalysts are mainly divided into four categories: precious metal and non-precious metal alloys, non-precious metal compounds, metal-nitrogen-carbon composite materials, and metal-free carbon-based materials. Its active metal components are mainly precious metals such as platinum, rhodium, palladium, iridium and cheap transition metals such as cobalt, iron, nickel, and manganese. Its material structure is mainly based on nanostructures, including nanoparticles, nanosheets, nanowires, nanoskeletons, nanocore-shell structures, etc. Nanostructures can significantly increase the specific surface area of particles, expose more active elements to participate in the reaction, and thus improve the quality activity and stability of the catalyst. But overall, the quality activity and stability of the above nanomaterials are still lacking and cannot meet commercial needs.
[0004] In order to solve the problems of mass activity and stability, preparing nanocatalysts into ultra-thin nanosheets with a thickness of only less than 5nm, that is, atomic-scale, has become a major research hotspot in recent years. Ultra-thin at the atomic scale (ultra-thin sheets with a thickness of less than 5nm) can expose the active atoms and reaction sites inside the particles to the greatest extent, thereby maximizing the mass activity of the catalyst. At the same time, the stability of the catalyst is improved by chemical bonds within the sheet plane. At present, domestic and foreign research institutions have successfully prepared a few precious metal alloys and a few transition metal atomic-level ultra-thin sheet catalysts through synthesis methods such as organic solvent thermal method, organic template method, layered precursor derivative method, and confined growth method. They have good stability and the electrocatalytic mass activity has also increased by dozens of times. However, to date, most materials have not yet achieved atomic-level ultra-thinness, and their catalytic activity and stability remain to be studied. Summary of the invention
[0005] The purpose of the present application is to provide an atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] An atomic-level ultrathin antiperovskite nanosheet electrocatalyst, having a general formula of A3BX, wherein A is one or more of Co, Fe, Ni, and Mn, B is In and / or Cu, and X is N;
[0008] The A3BX is a cubic crystal, and A and X form an A6X octahedral coordination structure;
[0009] The thickness of the atomically thin antiperovskite nanosheet electrocatalyst is 0.4-1.2 nm;
[0010] The method for preparing the atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst comprises:
[0011] Mix glycine and water, add sodium hydroxide aqueous solution to adjust the pH to 10-10.5, then add nitrate containing element A and nitrate containing element B dropwise under an inert gas atmosphere, react to obtain flocculent precipitation, and separate the solid and liquid to obtain a layered double metal hydroxide;
[0012] The layered double hydroxide is added to a formamide solution to obtain an LDH formamide dispersion, and then stirred under an inert gas atmosphere to obtain a formamide dispersion of a single-layer LDH;
[0013] The formamide dispersion of the monolayer LDH is mixed with sodium chloride, solid-liquid separation, drying, grinding, and then sintering in an ammonia atmosphere, and cooling to obtain a sintered product;
[0014] The sintered product is added into water, and the antiperovskite nanosheets on the water surface are collected after rotation stirring, and the atomic-level ultra-thin antiperovskite nanosheet electrocatalyst is obtained after repeating the process for multiple times.
[0015] Preferably, the atomically thin antiperovskite nanosheet electrocatalyst comprises an oxygen reduction catalyst Co3InN, Fe3InN, Mn3InN and a hydrogen evolution catalyst Ni3In 0.6 Cu 0.4 N.
[0016] Preferably, the amount of glycine used is 2.00-2.25 mmol / (140-160) ml water.
[0017] Preferably, the flow rate of the inert gas is 90-110 ml / min.
[0018] Preferably, the flow rate of the ammonia gas is 50-60 ml / min.
[0019] Preferably, the molar ratio of the nitrate containing element A to the nitrate containing element B is (0.73-0.77): (0.23-0.27).
[0020] Preferably, sodium hydroxide solution is added during the reaction to maintain the pH of the system at 10-10.5.
[0021] Preferably, the mass volume ratio of the layered double metal hydroxide to the formamide solution is (0.1-0.2) g: (100-200) ml;
[0022] The volume mass ratio of the formamide dispersion of the monolayer LDH to the sodium chloride is (20-30) ml: (20-30) g.
[0023] Preferably, the water is ultrapure water and is used after being boiled.
[0024] Preferably, the drying temperature is 100-120°C and the drying time is 10-12h;
[0025] The sintering temperature is 440-460° C. and the sintering time is 3-4 hours.
[0026] Compared with the prior art, the beneficial effects of this application include:
[0027] The atomic-level ultra-thin antiperovskite nanosheet electrocatalyst provided in this application has excellent hydrogen evolution, oxygen reduction activity and stability, and is expected to be used as a new catalyst in water electrolysis and hydrogen fuel cells. The preparation method of the atomic-level ultra-thin antiperovskite nanosheet electrocatalyst provided in this application uses a layered precursor peeling derivatization method to synthesize an atomic-level ultra-thin antiperovskite nanosheet catalyst with a thickness of only 0.4-1.2 nm for the first time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0029] Figure 1 is the X-ray diffraction analysis spectrum of the catalyst obtained in Example 1;
[0030] Figure 2 The X-ray diffraction analysis spectrum of the catalyst obtained in Example 2;
[0031] Figure 3 The X-ray diffraction analysis spectrum of the catalyst obtained in Example 3;
[0032] Figure 4 The X-ray diffraction analysis spectrum of the catalyst obtained in Example 4;
[0033] Figure 5 This is the X-ray diffraction analysis spectrum of the catalyst obtained in Comparative Example 1;
[0034] Figure 6 This is the X-ray diffraction analysis spectrum of the catalyst obtained in Comparative Example 2;
[0035] Figure 7 The thickness and morphology test spectrum of the catalyst obtained in Example 1;
[0036] Figure 8 The thickness and morphology test spectrum of the catalyst obtained in Example 2;
[0037] Fig. 9 The thickness and morphology test spectrum of the catalyst obtained in Example 3;
[0038] Fig.10 The thickness and morphology test spectrum of the catalyst obtained in Example 4;
[0039] Fig.11 This is a transmission electron microscope photo of the catalyst obtained in Comparative Example 1;
[0040] Fig.12 This is a transmission electron microscope photo of the catalyst obtained in Comparative Example 2;
[0041] Fig.13 Linear voltammetric scanning test curves of the catalyst obtained in Example, commercial platinum carbon, and the catalyst obtained in Comparative Example 1;
[0042] Fig.14 The constant voltage long-term stability test curves of the catalysts obtained in Example 1 and Example 2 and commercial platinum-carbon;
[0043] Fig.15 The constant voltage long-term stability test curves of the catalyst obtained in Example 3 and Comparative Example 1 and commercial platinum-carbon;
[0044] Fig.16 The LSV test curves of the atomically ultra-thin particles of Example 4 and Comparative Example 2 at room temperature;
[0045] Fig.17 This is the current-time curve of long-term constant voltage operation. DETAILED DESCRIPTION
[0046] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0047] Example 1
[0048] This embodiment provides an atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst, the chemical formula of which is Co3InN, and the preparation method is as follows:
[0049] 1. Synthesis of layered hydroxide LDH precursor
[0050] (1) Prepare 1000 ml of ultrapure water, boil it completely and remove trace carbonate and carbon dioxide, cool it down and store it in a sealed container for subsequent experiments. Dissolve high-purity sodium hydroxide (electronic grade purity, higher than 99.5%) in boiled ultrapure water to make a 1 mol / L sodium hydroxide solution, which is used for pH control during material synthesis.
[0051] (2) First, add 150 ml of boiling ultrapure water to a spherical flask, add 2.25 mmol of glycine and dissolve it, add 0.6 ml of the above sodium hydroxide solution, and adjust the pH to 10.1. Continuously introduce argon as a protective gas into the solution for 15 minutes at a flow rate of 100 ml / min to fully remove oxygen and carbon dioxide, effectively prevent the subsequent LDH precursor from being oxidized, and effectively prevent carbonate from hindering the subsequent stripping.
[0052] (3) According to the stoichiometric ratio of A3BX, prepare 0.75mmol of cobalt nitrate hexahydrate and 0.25mmol of indium nitrate tetrahydrate. First, dissolve cobalt nitrate hexahydrate and indium nitrate tetrahydrate in 20ml of boiling ultrapure water. Continuously introduce argon gas into the spherical flask at a flow rate of 100ml / min, keep the solution stirring at 420rpm, and drip the metal nitrate solution into the flask solution drop by drop to form a flocculent LDH precipitate. Add an appropriate amount of sodium hydroxide solution 6ml in time to maintain the pH at 10.2. After the addition is completed, continue stirring for 28min. Pour the product into a closed centrifuge tube for centrifugal separation and wash once (also with boiling ultrapure water). After pouring off the solution, obtain layered hydroxide LDH. Do not dry it, but store it in a sealed Ar protective gas in a state containing water.
[0053] 2. Formamide stripping
[0054] Take 0.15g of the above prepared LDH precipitate containing water and add it directly to 150ml of formamide solution to form a LDH formamide dispersion with a concentration of about 1mg / ml, and stir it for 16 hours at a magnetic stirring speed of 700rpm under Ar protective gas to disperse the LDH and fully peel it off, finally forming a formamide dispersion of a single layer of LDH.
[0055] 3. Sodium chloride adsorption sintering
[0056] Take 25 ml of the above dispersion, add 25 g of NaCl, stir well with a glass rod, dry under vacuum at 120°C for 12 hours, transfer the mixture to a mortar and grind it thoroughly, transfer it to a tube furnace, and sinter it at 450°C for 4 hours in an ammonia atmosphere. The ammonia flow rate is 60 ml / min. After sintering, cool the furnace to room temperature.
[0057] 4. Spin cleaning and separation
[0058] Take out the sintered product and add it to 500ml of deionized water. Water can dissolve sodium chloride. Stir with a magnetic rod at a speed of 900rpm. At this time, the water molecules will be thrown to the outside, and the ultra-thin antiperovskite nanosheets in the solution will spontaneously gather on the water surface of the central vortex. After rotating and stirring for 20 minutes, stop stirring, use a medicine spoon to collect the antiperovskite nanosheets on the central water surface (together with a small amount of solution), and transfer them to another clean beaker. Rotate and stir again, repeat 4 times, and most of the nanosheets can be collected and extracted.
[0059] The extracted nanosheets were added with 500 ml of clean deionized water again, and the above steps were repeated for one more rotation separation. Thus, the sodium chloride in the product can be removed as much as possible. The separated product was dispersed in 25 ml of formamide and sealed for storage.
[0060] Example 2
[0061] This embodiment provides an atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst, the chemical formula of which is Fe3InN, and the preparation method is as follows:
[0062] 1. Synthesis of layered hydroxide LDH precursor
[0063] (1) Prepare 1000 ml of ultrapure water, boil it completely and remove trace carbonate and carbon dioxide, cool it down and store it in a sealed container for subsequent experiments. Dissolve high-purity sodium hydroxide (electronic grade purity, higher than 99.5%) in boiled ultrapure water to make a 1 mol / L sodium hydroxide solution, which is used for pH control during material synthesis.
[0064] (2) First, add 150 ml of boiling ultrapure water to a spherical flask, add 2.20 mmol of glycine and dissolve it, add 0.8 ml of the above sodium hydroxide solution, and adjust the pH to 10.4. Continuously introduce argon as a protective gas into the solution for 13 minutes at a flow rate of 95 ml / min to fully remove oxygen and carbon dioxide, effectively prevent the subsequent LDH precursor from being oxidized, and effectively prevent carbonate from hindering the subsequent stripping.
[0065] (3) According to the stoichiometric ratio of A3BX, prepare 0.74mmol of ferric nitrate nonahydrate and 0.26mmol of indium nitrate tetrahydrate. First, dissolve ferric nitrate nonahydrate and indium nitrate tetrahydrate in 21ml of boiling ultrapure water. Continuously introduce argon gas into the spherical flask at a flow rate of 104ml / min, keep the solution stirring at 430rpm, and drip the metal nitrate solution into the flask solution drop by drop to form a flocculent LDH precipitate. Add an appropriate amount of sodium hydroxide solution 7ml in time to maintain the pH at 10.3. After the addition is completed, continue stirring for 30min. Pour the product into a closed centrifuge tube for centrifugal separation and wash once (also with boiling ultrapure water). After pouring off the solution, obtain layered hydroxide LDH. Do not dry it, but store it in a sealed Ar protective gas in a state containing water.
[0066] 2. Formamide stripping
[0067] Take 0.20g of the above prepared LDH precipitate containing water and add it directly to 200ml of formamide solution to form a LDH formamide dispersion with a concentration of about 1mg / ml, and stir it for 18 hours at a magnetic stirring speed of 650rpm under Ar protective gas to disperse the LDH and fully peel it, finally forming a formamide dispersion of a single layer of LDH.
[0068] 3. Sodium chloride adsorption sintering
[0069] Take 20 ml of the above dispersion, add 20 g of NaCl, stir well with a glass rod, dry under vacuum at 120°C for 10 hours, transfer the mixture to a mortar and grind it thoroughly, transfer it to a tube furnace, and sinter it at 450°C for 4 hours in an ammonia atmosphere. The ammonia flow rate is 50 ml / min. After sintering, cool the furnace to room temperature.
[0070] 4. Spin cleaning and separation
[0071] Take out the sintered product and add it to 450ml of deionized water. Water can dissolve sodium chloride. Stir with a magnetic rod at a speed of 800rpm. At this time, water molecules will be thrown to the outside, and the ultra-thin antiperovskite nanosheets in the solution will spontaneously gather on the water surface of the central vortex. After rotating and stirring for 15 minutes, stop stirring, use a medicine spoon to collect the antiperovskite nanosheets on the central water surface (together with a small amount of solution), and transfer them to another clean beaker. Rotate and stir again, repeat 4 times, and most of the nanosheets can be collected and extracted.
[0072] The extracted nanosheets were added with 500 ml of clean deionized water again, and the above steps were repeated for one more rotation separation. Thus, the sodium chloride in the product can be removed as much as possible. The separated product was dispersed in 30 ml of formamide and sealed for storage.
[0073] Example 3
[0074] This embodiment provides an atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst, the chemical formula of which is Mn3InN, and the preparation method is as follows:
[0075] 1. Synthesis of layered hydroxide LDH precursor
[0076] (1) Prepare 1000 ml of ultrapure water, boil it completely and remove trace carbonate and carbon dioxide, cool it down and store it in a sealed container for subsequent experiments. Dissolve high-purity sodium hydroxide (electronic grade purity, higher than 99.5%) in boiled ultrapure water to make a 1 mol / L sodium hydroxide solution, which is used for pH control during material synthesis.
[0077] (2) First, add 147 ml of boiling ultrapure water to a spherical flask, add 2.18 mmol of glycine and dissolve it, add 0.7 ml of the above sodium hydroxide solution, and adjust the pH to 10.3. Continuously introduce argon as a protective gas into the solution for 13 minutes at a flow rate of 102 ml / min to fully remove oxygen and carbon dioxide, effectively prevent the subsequent LDH precursor from being oxidized, and effectively prevent carbonate from hindering the subsequent stripping.
[0078] (3) According to the stoichiometric ratio of A3BX, prepare 0.73mmol of manganese nitrate tetrahydrate and 0.24mmol of indium nitrate tetrahydrate. First, dissolve manganese nitrate tetrahydrate and indium nitrate tetrahydrate in 20ml of boiling ultrapure water. Continuously introduce argon gas into the spherical flask at a flow rate of 108ml / min, keep the solution stirring at 400rpm, and drip the metal nitrate solution into the flask solution drop by drop to form a flocculent LDH precipitate. Add an appropriate amount of sodium hydroxide solution 6ml in time to maintain the pH at 10.2. After the addition is completed, continue stirring for 27min. Pour the product into a closed centrifuge tube for centrifugal separation and wash once (also with boiling ultrapure water). After pouring off the solution, obtain layered hydroxide LDH. Do not dry it, but store it in a sealed Ar protective gas in a state containing water.
[0079] 2. Formamide stripping
[0080] Take 0.10g of the prepared LDH precipitate containing water and add it directly to 100ml of formamide solution to form a LDH formamide dispersion with a concentration of about 1mg / ml, and stir it for 18 hours at a magnetic stirring speed of 600rpm under Ar protective gas to disperse the LDH and fully peel it, finally forming a formamide dispersion of a single layer of LDH.
[0081] 3. Sodium chloride adsorption sintering
[0082] Take 30 ml of the above dispersion, add 30 g of NaCl, stir well with a glass rod, vacuum dry at 110°C for 11 hours, transfer the mixture to a mortar and grind it thoroughly, transfer it to a tube furnace, and sinter at 440°C for 3 hours in an ammonia atmosphere. The ammonia flow rate is 60 ml / min. After sintering, cool the furnace to room temperature.
[0083] 4. Spin cleaning and separation
[0084] Take out the sintered product and add it to 400ml of deionized water. Water can dissolve sodium chloride. Stir with a magnetic rod at a speed of 850rpm. At this time, the water molecules will be thrown to the outside, and the ultra-thin antiperovskite nanosheets in the solution will spontaneously gather on the water surface of the central vortex. After rotating and stirring for 20 minutes, stop stirring, use a medicine spoon to collect the antiperovskite nanosheets on the central water surface (together with a small amount of solution), and transfer them to another clean beaker. Rotate and stir again, repeat 4 times, and most of the nanosheets can be collected and extracted.
[0085] The extracted nanosheets were added with 450 ml of clean deionized water again, and the above steps were repeated for one more rotation separation. Thus, the sodium chloride in the product can be removed as much as possible. The separated product was dispersed in 30 ml of formamide and sealed for storage.
[0086] Example 4
[0087] This embodiment provides an atomic-level ultra-thin antiperovskite nanosheet electrocatalyst with a chemical formula of Ni3In 0.6 Cu 0.4 N, the preparation method is as follows:
[0088] 1. Synthesis of layered hydroxide LDH precursor
[0089] (1) Prepare 1000 ml of ultrapure water, boil it completely and remove trace carbonate and carbon dioxide, cool it down and store it in a sealed container for subsequent experiments. Dissolve high-purity sodium hydroxide (electronic grade purity, higher than 99.5%) in boiled ultrapure water to make a 1 mol / L sodium hydroxide solution, which is used for pH control during material synthesis.
[0090] (2) First, add 156 ml of boiling ultrapure water to a spherical flask, add 2.14 mmol of glycine and dissolve it, add 0.7 ml of the above sodium hydroxide solution, and adjust the pH to 10.2. Continuously introduce argon gas into the solution as a protective gas for 14 minutes at a flow rate of 108 ml / min to fully remove oxygen and carbon dioxide, effectively prevent the subsequent LDH precursor from being oxidized, and effectively prevent carbonate from hindering the subsequent stripping.
[0091] (3) According to the stoichiometric ratio of A3BX, prepare 0.76mmol of nickel nitrate hexahydrate, 0.25mmol of indium nitrate tetrahydrate and copper nitrate trihydrate (0.15mmol of indium nitrate tetrahydrate and 0.1mmol of copper nitrate trihydrate). First, dissolve nickel nitrate hexahydrate, indium nitrate tetrahydrate and nitric acid trihydrate in 22ml of boiling ultrapure water. Continuously introduce argon gas into the spherical flask at a flow rate of 95ml / min, keep the solution stirring at 400rpm, and drip the metal nitrate solution into the flask solution drop by drop to form a flocculent LDH precipitate. Add an appropriate amount of sodium hydroxide solution 7ml in time to maintain the pH at 10.4. After the addition is completed, continue stirring for 30min. Pour the product into a closed centrifuge tube for centrifugal separation and wash once (also with boiling ultrapure water). After pouring off the solution, obtain layered hydroxide LDH. Do not dry it, but store it in a sealed Ar protective gas in a state containing water.
[0092] 2. Formamide stripping
[0093] Take 0.18g of the above prepared LDH precipitate containing water and add it directly to 180ml of formamide solution to form a LDH formamide dispersion with a concentration of about 1mg / ml, and stir it for 16 hours at a magnetic stirring speed of 700rpm under Ar protective gas to disperse the LDH and fully peel it, finally forming a formamide dispersion of a single layer of LDH.
[0094] 3. Sodium chloride adsorption sintering
[0095] Take 25 ml of the above dispersion, add 25 g of NaCl, stir well with a glass rod, vacuum dry at 120°C for 12 hours, transfer the mixture to a mortar and grind it thoroughly, transfer it to a tube furnace, and sinter it at 460°C for 4 hours in an ammonia atmosphere. The ammonia flow rate is 50 ml / min. After sintering, cool the furnace to room temperature.
[0096] 4. Spin cleaning and separation
[0097] Take out the sintered product and add it to 500ml of deionized water. Water can dissolve sodium chloride. Stir with a magnetic rod at a speed of 900rpm. At this time, the water molecules will be thrown to the outside, and the ultra-thin antiperovskite nanosheets in the solution will spontaneously gather on the water surface of the central vortex. After rotating and stirring for 18 minutes, stop stirring, use a medicine spoon to collect the antiperovskite nanosheets on the central water surface (together with a small amount of solution), and transfer them to another clean beaker. Rotate and stir again, repeat 4 times, and most of the nanosheets can be collected and extracted.
[0098] The extracted nanosheets were added with 500 ml of clean deionized water again, and the above steps were repeated for one more rotation separation. Thus, the sodium chloride in the product can be removed as much as possible. The separated product was dispersed in 25 ml of formamide and sealed for storage.
[0099] Comparative Example 1-2
[0100] Co3InN (Comparative Example 1) and Ni3In 0.6 Cu 0.4 N (Comparative Example 2) is used to illustrate that the above LDH peeling sintering method is not used, but the metal nitrate raw materials are directly mixed and ground, and sintered under an ammonia atmosphere at the same flow rate (100 ml / min), the same temperature (450°C), and the same time (4h). The powder materials obtained are all large particles of 100-500 nanometers. The oxygen reduction activity of the obtained Co3InN is significantly lower than that of the atomic-level ultra-thin Co3InN. The obtained Ni3In 0.6 Cu 0.4 The hydrogen evolution activity of N is also significantly lower than that of atomically thin Co3InN.
[0101] The obtained materials were analyzed as follows:
[0102] 1.XRD phase analysis
[0103] The first is the X-ray diffraction analysis spectrum, such as Figure 1 (Example 1), Figure 2 (Example 2), Figure 3 (Example 3), Figure 4 (Example 4), Figure 5 (Comparative Example 1), Figure 6 (Comparative Example 2). Combined with the crystal structure standard cards in the International Crystal Database (ICSD), the X-ray diffraction signals of each material correspond one-to-one with the standard diffraction lines in the database, which can prove that the obtained atomic-level ultra-thin materials, as well as the control group materials, are indeed antiperovskite phases Co3InN, Fe3InN, Mn3InN, Ni3In 0.6 Cu 0.4 N. These materials all have similar cubic structures and similar overall diffraction patterns. However, their unit cell sizes are slightly different, and the positions of their diffraction peaks are also slightly different. The unit cell parameters of the prepared materials are very close to the standard data in the database:
[0104] Co3InN, experimentally obtained a = b = c = 3.867 Å, cubic lattice, space group Pm-3m. The international database standard data is a = b = c = 3.860 Å, cubic lattice, space group Pm-3m.
[0105] Fe3InN, experimentally obtained a = b = c = 3.890 Å, cubic lattice, space group Pm-3m. International database standard data is a = b = c = 3.880 Å, cubic lattice, space group Pm-3m.
[0106] Mn3InN, experimentally obtained: a = b = c = 3.987 Å, cubic lattice, space group Pm-3m. International database standard data: a = b = c = 3.993 Å, cubic lattice, space group Pm-3m.
[0107] Ni3In 0.6 Cu 0.4 N, experimentally obtained is a = b = c = 3.846 Å, cubic lattice, space group Pm-3m. The international database standard data is a = b = c = 3.851 Å, cubic lattice, space group Pm-3m.
[0108] In addition, the comparative data are as follows:
[0109] Co3InN particles, experimentally obtained a = b = c = 3.853 Å, cubic lattice, space group Pm-3m. The international database standard data is a = b = c = 3.860 Å, cubic lattice, space group Pm-3m.
[0110] Ni3In particles 0.6 Cu 0.4 N, experimentally obtained is a = b = c = 3.857 Å, cubic lattice, space group Pm-3m. The international database standard data is a = b = c = 3.851 Å, cubic lattice, space group Pm-3m.
[0111] 2. Thickness analysis of ultra-thin materials
[0112] Use atomic force microscopy (AFM) to test the thickness and morphology of ultra-thin materials, such as Figure 7 (Example 1), Figure 8 (Example 2), Fig. 9 (Example 3) and Fig.10 (Example 4) is shown. The thickness of the slices in each test figure is measured and analyzed. Three ultra-thin slices are marked in each figure for illustration. The average thickness of Co3InN is about 0.4nm (about 400pm), which is equivalent to a single layer of lattice. The average thickness of Fe3InN is 1.25nm, about three layers of lattice. The average thickness of Mn3InN is 0.8nm, about two layers of lattice. Ni3In 0.6 Cu 0.4The average thickness of N is 0.6nm, which is about two layers of lattice. All four materials have reached the ultra-thin scale at the atomic level.
[0113] The samples in the comparative experiment are too thick to be measured by AFM, so we use TEM to qualitatively analyze their morphology and particle size. Fig.11 (Comparative Example 1), Fig.12 (Comparative Example 2) It can be seen that the comparative sample Co3InN is a random particle with a size of 100-200nm, while Ni3In 0.6 Cu 0.4 N is a cubic particle of 200-500nm in size. They are not ultra-thin sheets, and their thickness is much higher than the atomic-level ultra-thin scale. It should be noted that Fig.11 and Fig.12 The black color is the product particle. The particle size varies from 100 to 500 nm. In terms of thickness, the darker the particle, the thicker the particle. In experience, under TEM, the color of atomic-level ultra-thin materials (about 1nm thick) will be very light, even difficult to distinguish and observe. The color depth in the picture is obviously a particle with a thickness of at least tens of nanometers, or even hundreds of nanometers.
[0114] The above data fully proves the superiority and irreplaceability of the layered hydroxide LDH peeling sintering method in the synthesis of controlled morphology and thickness. Only this method can control the product morphology into a lamellar morphology and reduce the thickness to an atomic scale of around 1nm. Conventional synthesis methods can only obtain large particles of several hundred nanometers.
[0115] 3. Analysis of electrochemical catalytic performance
[0116] Atomic-level ultra-thin Co3InN, Fe3InN, and Mn3InN are used in the study of oxygen reduction catalytic performance, while Ni3In 0.6 Cu 0.4 N is used in the study of the catalytic performance of hydrogen evolution in water electrolysis.
[0117] In the oxygen reduction catalytic test, the linear voltammetric sweep (LSV) test was used to determine the starting potential of the material (i.e., the current density reached -0.1 mA·cm -2 The catalytic activity of the catalyst is evaluated by measuring the voltage corresponding to the time when the catalyst is charged (the negative sign only represents the current direction) and the limiting current density (the maximum stable current density that can be achieved within the test voltage range). The stability of the catalyst is evaluated by determining the degree of current attenuation through long-term constant voltage testing.
[0118] The test was conducted with commercial platinum-carbon Pt / C catalyst (Merck Sigma-Aldrich, 205931, carbon-supported platinum catalyst, Pt 5wt.%) as a reference. For a good catalyst, its starting potential should be as close as possible to that of platinum-carbon, and its limiting current should be close to or exceed that of platinum-carbon. In the constant voltage long-term operation test, the current attenuation should be less than that of platinum-carbon.
[0119] Fig.13 Linear voltammetry (LSV) tests of atomically thin materials, commercial platinum carbon, and control samples (oxygen reduction LSV test in 0.1M KOH solution). The starting potential of commercial platinum carbon is 0.99 V, and the limiting current is 4.7 mA·cm -2 The onset potential of Co3InN is 0.93 V and the limiting current is 5.3 mA·cm -2 The starting potential of Fe3InN is 0.92 V and the limiting current is 3.8 mA·cm -2 The onset potential of Mn3InN is 0.88 V and the limiting current is 3.5 mA·cm -2 The starting potential of the comparative Co3InN particles is 0.82 V and the limiting current is 2.5 mA·cm -2 .
[0120] The atomic-level ultra-thin Co3InN, Fe3InN, and Mn3InN have starting potentials and limiting currents close to commercial platinum carbon, and all have good oxygen reduction catalytic activity. Among them, Co3InN has the best activity, and its limiting current exceeds that of platinum carbon. Fe3InN and Mn3InN are next. The comparison sample Co3InN particles have the lowest starting potential, the smallest limiting current, and unsatisfactory oxygen reduction performance.
[0121] Constant voltage long-term stability test Fig.14 , Fig.15 As shown (in 0.1M KOH solution, the current-time curve with the operating voltage maintained at 0.75V, i.e., oxygen reduction stability test). The operating voltage was always 0.75V. After 30,000 seconds of continuous operation test, the current density of Co3InN decayed to 87%, Fe3InN decayed to 79%, Mn3InN decayed to 78%, and the comparison sample Co3InN particles decayed to 53%. Platinum carbon Pt / C was measured twice, and it decayed to 45% in turn. The other time it decayed to 40% in only 20,000 seconds. This shows that the stability of atomic-level ultra-thin Co3InN, Fe3InN, and Mn3InN is much higher than that of commercial platinum carbon, while the comparison sample Co3InN particles are only slightly better than commercial platinum carbon.
[0122] It can be seen that the atomic-level ultra-thin antiperovskite obtained by LDH peeling and sintering method is superior to commercial platinum carbon in oxygen reduction activity and stability, fully reflecting the composition and structural advantages of this type of compound. At the same time, it is also better than the large particles of the comparison sample, which also shows the superiority of this synthesis method in performance.
[0123] In terms of hydrogen evolution catalytic performance, the linear voltammetric sweep (LSV) test was also used to determine the hydrogen evolution overpotential (the international standard is a current density of 10 mA cm -2 The stability of the catalyst can be evaluated by running the test at constant voltage for a long time and determining the degree of current decay.
[0124] In the LSV test, after electrode correction, the zero point is the hydrogen evolution potential of standard commercial platinum carbon. The smaller the overpotential of the catalyst, the stronger the hydrogen evolution activity. Generally, an overpotential of less than 100mV can be considered to be a good hydrogen evolution catalytic performance.
[0125] Fig.16 These are LSV test graphs of the atomically ultra-thin particles of Example 4 and Comparative Example 2 at room temperature (hydrogen evolution LSV test in 1 M KOH solution). Fig.16 The temperatures in the figure are different sintering temperatures during the synthesis process. Atomic-level ultra-thin Ni3In4 synthesized at 450℃ 0.6 Cu 0.4 N at 10 mA cm -2 The overpotential at 600℃ is 95mV, which is less than 100mV, and it can be considered that the hydrogen evolution activity is good. The overpotential of the ultra-thin sample synthesized at 600℃ increases to 135 mV, and the activity decreases. However, both are better than the comparison sample Ni3In 0.6 Cu 0.4 N particles. The overpotentials of the comparison samples are 170 mV (synthesized at 450℃), 160 mV (synthesized at 600℃), and 200 mV (synthesized at 700℃). This indicates that the hydrogen evolution activity of the comparison samples is much lower than that of the atomic-level ultra-thin samples, and the activity is not good. The above fully illustrates the superiority of the atomic-level ultra-thin synthesis method in hydrogen evolution activity.
[0126] Fig.17 The current-time data of long-term operation at constant voltage (in 1 M KOH solution, the current-time curve with the operating voltage maintained at -0.1V, i.e., hydrogen evolution stability test). After 24 hours of continuous operation with the voltage maintained at -0.1V, the atomic-level ultra-thin Ni3In 0.6 Cu 0.4 N can still maintain 10 mA·cm -2 The current density of commercial platinum carbon has decayed to 7.0 mA cm -2 , demonstrating that atomically thin Ni3In 0.6 Cu0.4 N has better stability than commercial platinum carbon. (The activity of the comparison sample is too low, so no stability test is performed) The above shows the superiority of the atomic-level ultra-thin synthesis method in hydrogen evolution stability.
[0127] It can be seen that the atomic-level ultra-thin antiperovskite obtained by LDH peeling sintering method has excellent hydrogen evolution activity and better stability than commercial platinum carbon, which can reflect the composition and structural advantages of this type of compound. At the same time, the activity is better than the large particles of the comparison sample, which also shows the superiority of this synthesis method.
[0128] This application uses all cheap metals as raw materials, such as iron, cobalt, manganese, nickel, copper, etc., and does not contain precious metals. The material cost is much lower than the current commercial precious metal catalysts. The thickness of the prepared atomic-level ultra-thin antiperovskite materials is 0.6-1nm. Electrochemical test data confirms that the oxygen reduction and hydrogen evolution activities of antiperovskite are excellent, close to commercial precious metals, and the stability is better than commercial precious metals. At the same time, the activity and stability are also better than the granular materials prepared by conventional methods (comparison sample)
[0129] The synthesis method of the present application is simple and universal. The traditional solvothermal method needs to use different organic molecules or inorganic molecules as control agents to control the crystal face growth for different chemical systems and different crystal growth habits. The R&D investment is large, the organic or inorganic molecules used are relatively expensive, and they are not universal. Once the catalyst element is replaced, the control agent needs to be re-screened. The present application directly uses double metal hydroxide precipitation as a precursor. After peeling and separation, a monolayer hydroxide with a thickness of 0.6-1.2nm is first obtained, and then the monolayer hydroxide is directly sintered. With the help of the confinement effect of its monolayer morphology, an atomic-level ultra-thin antiperovskite with a thickness of 0.4-1.2nm is directly obtained. The synthesis route is simple, does not require the use of any control agent, and is applicable to different elements.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An atomically thin antiperovskite nanosheet electrocatalyst, characterized in that: The general formula is A3BX, wherein A is one or more of Co, Fe, Ni, and Mn, B is In and / or Cu, and X is N; The A3BX is a cubic crystal, and A and X form an A6X octahedral coordination structure; The thickness of the atomically thin antiperovskite nanosheet electrocatalyst is 0.4-1.2 nm; The method for preparing the atomic-level ultra-thin anti-perovskite nanosheet electrocatalyst comprises: Mix glycine and water, add sodium hydroxide aqueous solution to adjust the pH to 10-10.5, then add nitrate containing element A and nitrate containing element B dropwise under an inert gas atmosphere, react to obtain flocculent precipitation, and separate the solid and liquid to obtain a layered double metal hydroxide; The layered double hydroxide is added to a formamide solution to obtain an LDH formamide dispersion, and then stirred under an inert gas atmosphere to obtain a formamide dispersion of a single-layer LDH; The formamide dispersion of the monolayer LDH is mixed with sodium chloride, solid-liquid separation, drying, grinding, and then sintering in an ammonia atmosphere, and cooling to obtain a sintered product; The sintered product is added into water, and the antiperovskite nanosheets on the water surface are collected after rotation stirring, and the atomic-level ultra-thin antiperovskite nanosheet electrocatalyst is obtained after repeating the process for multiple times.
2. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: Including oxygen reduction catalyst Co3InN, Fe3InN or Mn3InN and hydrogen evolution catalyst Ni3In 0.6 Cu 0.4 N.
3. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: The amount of glycine used is 2.00-2.25 mmol / 140-160 mL water.
4. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: The flow rate of the inert gas is 90-110 mL / min.
5. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: The flow rate of the ammonia gas is 50-60 mL / min.
6. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: The molar ratio of the nitrate containing element A to the nitrate containing element B is 0.73-0.77:0.23-0.
27.
7. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: During the reaction, sodium hydroxide solution is added to maintain the pH of the system at 10-10.
5.
8. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: The mass volume ratio of the layered double metal hydroxide to the formamide solution is 0.1-0.2 g: 100-200 mL; The volume mass ratio of the formamide dispersion of the monolayer LDH to the sodium chloride is 20-30 mL: 20-30 g.
9. The atomically thin antiperovskite nanosheet electrocatalyst according to claim 1, characterized in that: The water used for mixing glycine and water is ultrapure water, which is used after being boiled.
10. The atomically thin antiperovskite nanosheet electrocatalyst according to any one of claims 1 to 9, characterized in that: The drying temperature is 100-120°C and the drying time is 10-12h; The sintering temperature is 440-460° C. and the sintering time is 3-4 hours.
Citation Information
Patent Citations
Method for preparing perovskite-like composite metallic oxide by lamina
CN101041472A
CuNCo3 type electrocatalytic oxygen evolution catalyst with anti-perovskite structure and preparation method of CuNCo3 type electrocatalytic oxygen evolution catalyst
CN109638305A